Occupational Class Groups as a Risk Factor for Genitourinary Cancer - A Matched Case-Control Study - Mashallah Aghillinejad; Elaheh Kabir Mokamelkhah; Zahra Imanizadeh; Hossein Danesh (Iranian Journal of Health, Safety and Environment, 2016)
Cancer is a disease with huge consequences for patients and their families. It has a high mortality rate in both developed and developing countries. Eleven to 15 percent of all cancers can be attributed to occupational risk factors. The aim of this pilot study was to define the risks of specific occupational classes based on the International Standard for the Classification of Occupations 2008 (ISCO-08) in causing genitourinary (GU) cancer. A matched case-control study was designed and 208 cancer patients were interviewed by a single physician. Controls were selected from cancer patients with different cancers. For assessment of lifestyle, the simple lifestyle indicator questionnaire was. Years of working until 5 years before the diagnosis were questioned and later categorized by the ISCO classification In total 156 GU cases and non-genitourinary cancer patients were selected. The mean age at the time of diagnosis was 51.01 years for both groups. Except the platelet count, there was no significant difference between the groups. Some ISCO classes (1, 2, and 0) were eliminated because of low numbers. The difference between working in different classes of ISCO classification (3 through 9) was not associated with the occurrence of genitourinary cancer. No significant difference was found between the occupational classes in patients with genitourinary cancer and controls.